Legality and Effectiveness of the DPR’s Aspiration Network System under Administrative Law - Ihsanul Maarif; Firdaus Arifin; Luma Ali Faraj Al Dhaheri; Novendri M. Nggilu; M. Yasin Al Arif (TRUNOJOYO LAW REVIEW, 2026)
The public aspiration management system within Indonesia’s House of Representatives (DPR) operates without a clear framework rooted in administrative law, resulting in procedural ambiguity, weak institutional accountability, and limited meaningful public participation. The aim of this study is to analyze the normative and institutional shortcomings of the House of Representatives’ consultation system; consequently, it seeks to contribute by proposing a conceptual framework grounded in administrative law. Employing normative legal research with a conceptual and statutory approach, this study also draws on a qualitative analysis of institutional documents and academic literature. The findings revealed the absence of standardized regulations governing aspiration procedures, which rendered the system discretionary and resistant to objective evaluation. Aspirations are treated as political functions rather than administrative obligations, undermining the legitimacy of legislative representation. The study recommends institutional and regulatory reforms, including the development of standard operating procedures, a digital aspiration tracking system, and the integration of accountability principles into legislative ethical codes. These findings not only expose institutional deficiencies but also reconceptualize the DPR’s aspiration system within the framework of administrative law. A key theoretical contribution lies in extending the scope of administrative law beyond the executive branch to legislative institutions, particularly in the governance of public participation. Public aspirations are reframed as administrative rights and forms of public service rather than merely political functions. The introduction of a “limited administrative embedding” model provides a structured approach to integrating administrative principles into legislative functions without diminishing their political character.